Apoplastic immunity and its suppression by filamentous plant pathogens. Issue 4 (17th April 2013) - Doehlemann, Gunther; Hemetsberger, Christoph
<x xml:space="preserve">Abstract</x> <table-wrap position="anchor" orientation="portrait"> <x xml:space="preserve">Table </x> 1001 I. I. 1001 II. II. 1003 III. III. 1004 IV. IV. 1005 V. V. 1006 VI. VI. 1007 VII. VII. 1011 1011 References 1011 </table-wrap> Summary Microbial plant pathogens have evolved a variety of strategies to enter plant hosts and cause disease. In particular, biotrophic pathogens, which parasitize living plant tissue, establish sophisticated interactions in which they modulate the plant's metabolism to their own good. The prime decision, whether or not a pathogen can accommodate itself in its host tissue, is made during the initial phase of infection. At this stage, the plant immune system recognizes conserved molecular patterns of the invading microbe, which initiate a set of basal immune responses. Induced plant defense proteins, toxic compounds and antimicrobial proteins encounter a broad arsenal of pathogen‐derived virulence factors that aim to disarm host immunity. Crucial regulatory processes and protein–protein interactions take place in the apoplast, that is, intercellular spaces, plant cell walls and defined host–pathogen interfaces which are formed between the plant cytoplasm and the specialized infection structures of many biotrophic pathogens. This article aims to provide an insight into the most important principles and components of apoplastic plant immunity and its modulation by filamentous microbial pathogens.